Valuing the social? The nature and controversies of measuring social return on investment (SROI) - Arvidson, Malin; Lyon, Fergus; McKay, Stephen; Moro, Domenico (Voluntary sector review, 2013)
The concept of 'social return on investment' (SROI) has come to play an important role in debates about how social enterprises and charities conceptualise, measure and communicate their achievements. In this paper we analyse the nature and role of SROI as used in the United Kingdom for impact assessment of such organisations. The paper offers insight into methodological and procedural aspects of the framework. Key issues explored include the quantification of benefits, the valuing of volunteering and the ways in which judgement and discretion are exercised. There is a particular tension between the participatory element in the design of each SROI exercise and its use for the purpose of competition. The paper concludes by proposing a research agenda that includes an examination of the context in which discretion and judgement are applied and the use and usefulness of SROI in the new policy and funding environment in which third sector organisations currently find themselves.